A study of the financial and accounting systems of Selangor State Treasury / Othman Mohd. Salleh - Mohd. Salleh, Othman (1988)
This paper is only confined to the Selangor State Treasury as a representative of all the State Treasuries in Malaysia. At the time of data collections, the State Treasury was busy with the 1939 budget preparation, examinations and consolidation and the Auditor General was in turn busy with their annual reports as such I was only able to spend limited time with them.